Self-Efficacy as Determinant of Interest Becoming Intensive Care Nurse - Metalita, Eva; Handiyani, Hanny; Kuntarti, Kuntarti; Afriani, Tuti; Nurdiana, Nurdiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the factors that influence interest in becoming an intensive nurse. The design of this study used a cross-sectional approach. The results showed self-efficacy, appreciation, work unit, age, family support and supervisor support (p=<0.001), years of service (p=0.005), gender (p=0.002), career level (p=0.004), and experience. Training (p=0.003) affected the interest of intensive nurses. On the other hand, knowledge and level of education were not influenced by the pull of intensive nurses. The results of multiple linear regression analysis found that the most influential interest factors in becoming an intensive nurse were self-efficacy, followed by rewards, work units, and gender. These four factors contributed 57.4% in influencing the interest in becoming an intensive nurse. In conclusion, what most determines interest in becoming an intensive nurse is self-efficacy. Keywords: Determinants, Interests, ICU Nurse